Long-Term Effectiveness of Onabotulinum Toxin-A in a Combined Total Endoscopic Management of Pediatric Vesicoureteral Reflux in Neurogenic Bladder Dysfunction - Claudio Paratore; Chiara Pellegrino; Noemi Deanesi; Rebecca Pulvirenti; Maria Luisa Capitanucci; Giovanni Mosiello (Toxins, 2025)
Vesicoureteral reflux (VUR) management in children with neurogenic bladder dysfunction (NBD) remains a clinical challenge. Total endoscopic management (TEM), combining intradetrusor Onabotulinum Toxin-A (BTX-A) and subureteric dextranomer/hyaluronic acid (Deflux(R)) injection, offers a minimally invasive alternative. The aim of this retrospective study is to evaluate the long-term effectiveness of TEM. Inclusion criteria: symptomatic II–V grade VUR (also I in bilateral VUR) in NBD children with follow-up ≥12 months. Nineteen patients were enrolled, 24 ureters (grade I–II: 2, grade III–V: 22); 5 patients (20.8%) had bilateral VUR. Mean age at surgery: 7.6 years (1.3–17). No complications were reported. TEM was effective in 11 patients (57.9%), 3/11 requiring a second TEM treatment. VUR resolution appeared in 14 ureters (58.3%), downgrading in 6 (42.9%), persistence in 4 (28.6%). Among non-responders’ patients (8/19, 42.1%), five (26.3%) required bladder augmentation (one combined with ureteral reimplantation), one (5.3%) underwent reimplantation, and two (10.5%) continued conservative management. At bladder biopsy, 11 patients (57.9%) had chronic inflammation, 8 (42.1%) showed fibrosis; no difference in success rate was recorded. All responders required repeated BTX-A injections. Mean follow-up: 3.2 years (range 1–4.7). In selected patients, TEM appears to be a safe and effective strategy, potentially delaying or avoiding major reconstructive surgery.